Autofluorescence properties of murine embryonic stem cells during spontaneous differentiation phases. Issue 9 (30th September 2013) - Santin, Giada; Paulis, Marianna; Vezzoni, Paolo; Pacchiana, Giovanni; Bottiroli, Giovanni; Croce, Anna C.
ABSTRACT Background and Objective The autofluorescence (AF) analysis allows in vivo, real‐time assessment of cell functional activities, depending on the presence of biomolecules strictly involved in metabolic reactions and acting as endogenous fluorophores. Pluripotent stem cells during differentiation are known to undergo changes in their morphofunctional properties, with particular reference to bioenergetic metabolic signatures involving endogenous fluorophores such as NAD(P)H, flavins, lipofuscin‐like lipopigments. Since the development of regenerative therapies based on pluripotent cells requires a careful monitoring of the successful maturation into the desired phenotype, aim of our work is to evaluate the AF potential to assess the differentiation phases in a murine stem cell model. Study Design/Materials and Methods Mouse embryonic stem cells (ESCs) maintained with and without leukemia inhibitory factor (LIF), embryoid bodies (EBs), and EB‐derived cells undergoing spontaneous differentiation toward the hematopoietic lineage have been used as a sample models. Cell AF properties have been characterized upon 366‐nm excitation, under living conditions and in the absence of exogenous markers. Imaging, microspectrofluorometric techniques, and spectral fitting analysis based on the spectral parameters of each endogenous fluorophore have been applied to estimate their contribution to the whole cell AF emission spectra. Specific cytochemical labeling has been performed to validate AF data. Results Depending on the differentiation phases, cells undergo changes in morphology, AF distribution patterns, and AF emission spectral profiles. These latter reflect variations in the single endogenous fluorophore contribution to the overall emission. The coenzyme NAD(P)H accounts for up to 80% of the whole spectral area. The free form prevails on the bound one, and their changes have been investigated in terms of NAD(P)Hbound/free and redox ratios. These values vary in agreement with a slow metabolic activity and prevailing glycolytic metabolism in the undifferentiated HM1 cells, an increased metabolic activity still relying on glycolysis during the early differentiation phases, and an increased oxidative phosphorylation in EB and hematopoietic precursor cells. Lipofuscin‐like lipopigments decrease following differentiation, and porphyrins contributing for less than 5%, prevail in the more actively differentiating cells. These results reflect the shift between anaerobic and aerobic respiration following differentiation, consistently with a decreased autophagy of cell organelles (i.e., mitochondria, as a strategy reported in the literature to keep the undifferentiated homeostasis state), higher mitochondrial activity with more numerous NADH binding sites and synthesis of heme as prosthetic group of proteins, that is, cytochromes. Conclusions These data open promising perspectives for the monitoring of stem cells differentiation under living conditions without labeling with exogenous agents (inducing perturbations when used in vivo), or immunomarkers not always available for veterinary and zootechnics, by exploiting endogenous fluorophores as intrinsic biomarkers of cell morphofunctional changes. Lasers Surg. Med. 45:597–607, 2013. © 2013 Wiley Periodicals, Inc.